2011
DOI: 10.1088/1674-1137/35/1/017
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of ion beam extraction and focusing system

Abstract: The characteristics of ion beam extraction and focused to a volume as small as possible were investigated with the aid of computer code SIMION 3D version 7. This has been used to evaluate the extraction characteristics (accel-decel system) to generate an ion beam with low beam emittance and high brightness. The simulation process can provide a good study for optimizing the extraction and focusing system of the ion beam without any losses and transported to the required target. Also, a study of a simulation mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…11, where the electric field is optimal for focusing the beam at this hole diameter Fig. 13 depicts the relationship between the extractor holes and beam diameter, in which the beam diameter is proportional to the extraction voltages and the hole diameter as well, [8] as a consequence of reducing ion losses at the electrodes' edges, on the other hand, the beam diameter is inversely proportional to extraction voltage. The simulation and experimental measurements of an efficient ion beam extracted from the newly source agreed well.…”
Section: Experimental Investigations and Resultsmentioning
confidence: 99%
“…11, where the electric field is optimal for focusing the beam at this hole diameter Fig. 13 depicts the relationship between the extractor holes and beam diameter, in which the beam diameter is proportional to the extraction voltages and the hole diameter as well, [8] as a consequence of reducing ion losses at the electrodes' edges, on the other hand, the beam diameter is inversely proportional to extraction voltage. The simulation and experimental measurements of an efficient ion beam extracted from the newly source agreed well.…”
Section: Experimental Investigations and Resultsmentioning
confidence: 99%
“…are given. In addition, it can simulate time of flight, mass spectrometry, quadrupole, ion source, optical detector and other more complex physical models [13,15].…”
Section: The Simion Simulation Softwarementioning
confidence: 99%
“…Additionally, they described the possible plasma boundary curvatures during ion extraction. [7] Dorf et al investigated the relationship between the extracted beam current and plasma density, and suggested that beam formation in the plateau regime could suppress noise and stabilize the extracted current. [8] Keller observed the process of ion beam formation and the extraction system for high-current beams extracted from plasma ion sources.…”
Section: Introductionmentioning
confidence: 99%